A study about wayfinding design of Mini Malaysia and ASEAN Cultural Park / Athirah A. Wahab and Zahara Ramli - A. Wahab, Athirah; Ramli, Zahara (Kolej Pengajian Seni Kreatif (KPSK) UiTM Cawangan Melaka, 2023)
Wayfinding design is the important items for every place such as museum, theme park and shopping malls. Decisions about where to go must be made quickly, and anxiety-induced stress may confuse problem-solving behavior of people (Passini,1996). The solution for making decision problems is by having an efficient wayfinding design helps people to go through the places with right direction. For instance, Mini Malaysia and Asean Cultural Park is the big place that have many routes and checkpoints. They are one of the cultural park that have many mini replicas of Malaysia traditional houses. Other than that, they also have cultural entertainment and activities. Based on the activities and the placement of mini traditional house shows that Mini Malaysia and Asean Cultural Park have many routes that might take time for visitor to walk through. In order to help visitor to make decision and guide them to the right path, they need to have an efficient layout design of wayfinding.